THE EFFECT OF FITNESS EXERCISE ON ANAEROBIC POWER AND AEROBIC POWER - Ciekurs, Kalvis; Arnis, Voldemārs; Bernāns, Edgars; Kaupuzs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
There are many discussions about how to increase anaerobic power and anaerobic power capacity in cross-country skiing. Many scientists research the possibilities of increasing anaerobic power and anaerobic power capacity in this sport. The aim was to research the possibilities of increasing anaerobic power and anaerobic power capacity. A pilot study was carried out. Two BJSS "Arkādija" cross-country skiing specialization participants (15 years old girl (G) and boy (B)) participated in the study. The following methods were used in the study: test exercises (bench press, leg press, push up, pull down, pull up), WO2 max, Skierg Concept-2, Skierg Thorax and mathematical statistics. Fitness exercises used one month after that three month period of endurance exercise and last month fitness exercises again. The results: having stated the result difference before fitness exercises and after it. The participant G and B results difference in anaerobic power test was 48,7% and 37,1% and aerobic power test results was 39,8% and 32,4%. Conclusions: the obtained data from both BJSS “Arkādija” specialization participants prove that after the fitness exercise periods the results have improved. The results testify significant improvement of double pooling results on skiergs, what is showed by the difference of the mean results.